The Effects of Different Light Qualities on Gamma Ray-Treated Scenedesmus - Arañez, Adoracion (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 1 (1992), 2007)
Unialgal culture of Scenedesmus quadricauda (Turp.) Breb. suspended in distilled water was treated with 0 Gy (control), 40 Gy, 80 Gy, and 120 Gy gamma rays from a to 60 Co source at Philippine Nuclear Research Institute, placed in one-liter flasks, enough Bold basal medium added to give a transmittance of 97% determined by using a spectrophotometer, kept in the dark for 24 hrs., then placed in vials and distributed equally in three growth chambers with white light, red light, and blue light. The lighting was continuous with algae subjected to the same light intensity, and the temperature maintained at 30±1° C. A sterile regimen was followed. For the first two weeks, the growth rates of algae under white light were highest, followed by those under red light, while those grown under blue light had the lowest growth rate. After the second week, differences in growth rates were not significant anymore. During the first week, generally low doses of gamma radiation had stimulating effects on growth rates while high doses had inhibitory effects on growth. The abnormal Scenedesmus observed were enlarged cells of normal shape in coenobia of two cells and four cells, enlarged cells that were not forming coenobia, coenobia composed of enlarged cells of abnormal shape, coenobia composed of enlarged cells of different sizes, cells with kidney-shape chloroplast, coenobia with cells that were not in alignment as in the normal ones, and cells that were colorless. Percentage of coenobia with enlarged cells determined one week after the treatment showed that higher doses generally produced more enlarged cells than lower doses. Treated algae grown in red light and blue light which showed lesser growth rates than those under white light had higher percentage of enlarged cells. Enlarged cells of normal shape were successfully propagated for more than ten generations.